Object-oriented test & measurement software development in C++ : - Atchison, Lee (Prentice Hall PTR, 1997)
A book/CD-ROM introduction to C++ concepts in a framework designed to suit the concerns of the test and measurement community. After a general overview of classical test systems, Parts II and III describe fundamentals of object-oriented programming and how they are applied to test and measurement systems. Includes a complete working example of a test system, plus chapter exercises and answers. The CD-ROM contains examples of C++ code.